Multimodality to improve Security and Privacy in Fingerprint Authentication System - Islam, Md. Rajibul; Sayeed, Md. Shohel; Samraj, Andrews (2007)
With the pace of increasing online transactions and communication, the demand for security and privacy increases. To protect confidential information and to authenticate people electronically, several solutions already introduced. Traditional biometric systems that are based on single biometric usually suffer from problems like impostors' attack or hacking, unacceptable error rates. To improve security and privacy and system's reliability two or more biometrics of the same identity could be combined in a method that enhances the efficiency of the system. The biometric information, however, is irreplaceable information, when it is compromised. Thereby, one must give a special attention to protection of such information. We propose a novel protection technique for the biometric information, especially the feature information and the templates. The point of our proposal is securely embeds and extracts an iris template in a fingerprint image using a combined DWT and LSB based biometric watermarking algorithm in each authentication. The embedded data travel through insecure communication line like the internet, and they are used in matching process. This technique causes security against eavesdropping and replay attacks on the internet, because the watermark embedded transmitted data are used in the authentication session after watermark extraction.